AIR Project Final Report - Rufino, José (2009)
This document describes the main results of AIR, an innovation initiative sponsored by ESA, the European Space Agency. The acronym AIR stands for ARINC 653 Interface in RTEMS. The ARINC 653 is a civil aviation world specification addressing safety critical and certification issues in embedded systems software. The AIR Project studied the adoption of ARINC 653 in space on-board software together with the utilization of RTEMS, the Real-Time Executive for Multiprocessor Systems. This document: (i) describes the main issues regarding the AIR architecture specification; (ii) addresses how space and time partitioning could be provided in an abstract processor infrastructure, as well as those requirements can be mapped into both SPARC ERC32/LEON and Intel IA-32 (80x86) architectures; (iii) describes how to achieve the mapping of the ARINC 653 service interface in RTEMS; (iv) identifies the most relevant module dependencies of RTEMS with regard to AIR implementations; (v) identifies a preliminary set of modifications to be introduced in the RTEMS application production chain for the implementation of AIR-based systems (exemplified through a proof of concept prototype)